OS 13-08 ASSOCIATION OF CARDIAC STRUCTURE AND FUNCTION WITH CENTRAL AND BRACHIAL BLOOD PRESSURE VARIABILITY IN HYPERTENSIVE PATIENTS: THE SAFAR STUDY. (September 2016) - Zhang, Yi; Chi, Chen; Yu, Shikai; Argyris, Antonis; Blacher, Jacques; Safar, Michel; Protogerou, Athanase
Abstract : Objective: Both brachial blood pressure (BP) level and its variability (BPV) have significant association with cardiac structure and function. Recent studies indicated that central BP was superior to brachial BP in the association with cardiac abnormities. However, it remains unknown that whether central BPV is better associated with cardiac structure and function. We were, therefore, aimed to investigate and compare central and brachial BPV, in terms of the identification of cardiac abnormities. Design and Method: 445 consecutive outpatientsfor consultation on hypertension were recruited and 203 participants undergoing echocardiography were included in the present analysis. Twenty-four hour ambulatory BP was measured by a validated BP monitor (Mobil-O-Graph, Stolberg, Germany). Left ventricular (LV) mass and LV diastolic dysfunction (LVDD) were evaluated by echocardiography. Results: After adjustment for age, gender, body mass index, smoke, hypertension and mean 24hr BP, central average real variability (ARV), but not 24hr weighted standard deviation (wSD, brachial or central) or brachial ARV, was significantly associated with LV mass index (LVMI) (P = 0.02). Similar result was found in multivariate logistic regression. Only central ARV significantly associated with LV hypertrophy (P = 0.04). As for LVDD, not the brachial or central 24hr wSD, but the central and brachial ARV, associated with LVDD significantly, with OR = 2.28 and OR = 2.36, respectively. Conclusions: In summary, central BPV, especially the central ARV, shows its superiority over brachial BPVs, in terms of cardiac structure and function.